2012
DOI: 10.1089/dia.2011.0302
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Acarbose and Dietary Modifications to Limit Glycemic Variability Following Roux-en-Y Gastric Bypass as Assessed by Continuous Glucose Monitoring

Abstract: Dietary counseling and acarbose treatment eliminated the symptoms and improved the CGM profile of patients suffering from dumping syndrome after RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 21 publications
1
45
0
2
Order By: Relevance
“…Hence, the need to work with few samples in health and biological sciences is growing, prompting statisticians to improve their methods. In current study, with only one experimental unit (a single rat), it was possible to obtain results similar to those of other studies which reported the effect of acarbose on glycaemia carried out with larger samples (Coniff et al, 1995;Pereira et al, 2011;Ritz et al, 2012;Rosak et al, 2002;Scheen et al, 1994;Sybuia et al, 2014Sybuia et al, -2015Wong & Jenkins, 2007;Yee & Fong, 1996).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Hence, the need to work with few samples in health and biological sciences is growing, prompting statisticians to improve their methods. In current study, with only one experimental unit (a single rat), it was possible to obtain results similar to those of other studies which reported the effect of acarbose on glycaemia carried out with larger samples (Coniff et al, 1995;Pereira et al, 2011;Ritz et al, 2012;Rosak et al, 2002;Scheen et al, 1994;Sybuia et al, 2014Sybuia et al, -2015Wong & Jenkins, 2007;Yee & Fong, 1996).…”
Section: Resultssupporting
confidence: 87%
“…However, some organic compounds, among them acarbose, may inhibit the activity of these enzymes (Geng & Bai, 2008;Ritz et al, 2012) and thus prevent or attenuate hyperglycemic peaks (Coniff, Shapiro, Seaton, & Bray, 1995;Pereira et al, 2011;Scheen, Magalhaes, Salvatore, & Lefebvre, 1994;Sybuia, Guilhermetti, Mangolim, Bazotte, & Matioli, 2014-2015Wong & Jenkins, 2007). Acarbose has been widely studied for the treatment of Type 2 diabetes (Ritz et al, 2012;Rosak, Haupt, Walter, & Werner, 2002;Yee & Fong, 1996) as a therapeutic agent added to food or as a drug administered orally (Espín, García-Conesa, & Tomás-Barberán, 2007;Eng Kiat Loo & Huang, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have been published regarding the usefulness of a low-carbohydrate diet and α-GI for late dumping syndrome (6)(7)(8)(9)(10)(11). Among these, four using CGM revealed that a low-carbohydrate diet and α-GI effectively decreased the frequency of hypoglycemia and the fluctuation of blood glucose after gastric surgery (5)(6)(7)11).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, four using CGM revealed that a low-carbohydrate diet and α-GI effectively decreased the frequency of hypoglycemia and the fluctuation of blood glucose after gastric surgery (5)(6)(7)11). On the other hand, there is a report that miglitol was effective for reactive hypoglycemia secondary to late dumping syndrome, but not acarbose and voglibose (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation